THE COMPATIBILITY OF OUTDOOR STUDY APPLICATION OF ENVIRONMENTAL SUBJECT USING PSYCHOLOGICAL THEORIES OF INTELLIGENCE AND MEANINGFUL LEARNING IN SENIOR HIGH SCHOOL - Eko Harianto; La Ode Nursalam; Fahrudi Ahwan Ikhsan; Z Zakaria; D Damhuri; Andri Estining Sejati (Department of Geography Education, University of Jember, 2019)
The problem in this research relates to the learning theory that rarely considered as a basis in learning in Indonesia. learning plans and syllabus structure in the national curriculum is not included learning theory point. learning theory only has been less studied in the subjects in geography education undergraduate. This makes learning theory material less explored. Learning theory is also often forgotten in educational research undergraduate and postgraduate programs. Many research did not allude to the relevance of learning theory in learning. After graduating, they less develop or linking learning theory with the teaching profession. That condition makes learning essence should be strengthened to become weak or even disappear.This research aims to describe the compatibility when applying outdoor study environment subjects with the psychological theories of intelligence and meaningful learning theory in senior high school. This research used a qualitative methodology with the type of descriptive exploitative research. Data sources are students and geography teachers. The process of collecting data uses the method of observation and interviews. Data were analyzed with the 6 Cresswell's qualitative analyzing steps. The results show that the application of outdoor study is suitable both the psychological theories of intelligence and meaningful learning. The compatibility is reflected in the learning activities, there are: before, during, and after working in the outdoor. The teacher's ability to implement the basis of psychological theories of intelligence and meaningful learning makes learning more easily understood and meaningful for students. Keywords: meaningful learning, outdoor study, psychological theories. References Agra et al. (2019). Analysis of The Cocept of Meaningful Learning in Light of The Ausubel’s Theory. Rev Bras Enferm 72(1), 248-255. Anderson, L.W., & Krathwohl, D.R. (2015). Kerangka Landasan untuk Pembelajaran, Pengajaran, dan Asesmen Revisi Taksonomi Pendidikan Bloom (Translate. Priantoro, A.). Yogyakarta: Pustaka Pelajar. Arikunto, S. (2016). Prosedur Penelitian Suatu Pendekatan Praktik. Jakarta: Rineka Cipta. Arsyad, A. (2014). Media Pembelajaran. Jakarta: PT Raja Grafindo Persada. Badakar, C.M et al. (2017). Evaluation of The Relevance of Piaget’s Cognitive Principles among Parented and Orphan Children in Belagavi City, Karnataka, India: A Comparative Study. Int J Clin Prediatr Dent. 10(4), 356-350. Becker et al. (2017). Effects of Regular Classes in Outdoor Education Settings: A Systematic Review on Student’s Learning, Social and Health Dimensions. International Journal of Environmental Research and Public Health 14(5), 485 1-20. Boyes, M & Potter, T. (2015). The Application of Recognition-Primed Decision Theory to Decisions Made in An Outdoor Education Contect. Australian of Outdoor Education 18(1), 2-15. Cooper, A. (2015). Nature and The Outdoor Learning Environtment: The Forgotten Resource in Early Childhood Education. International Journal of Early Chilhood Environmental Education 3(1), 85-97. Cresswell, J.W. (2016). Research Design Pendekatan Kualitatif, Kuantitatif, dan Mixed. Yogyakarta: Pustaka Pelajar. Dillon, J. et al. (2017). Toward a Convergence between Science and Environmental Education. Abigdon: Taylor & Francis. Ensar, f. (2014). How Children Construct Literacy: Piagetian Perspective. International Journal of Secondary Education 2(2), 34-39. Erika, S. & Satu, U. (2018). Transformational Elements for Learning Outdoors in Finland: A Review of Research Literature. International Journal of Research Studies in Education 7(3), 73-84. Gilchrist, M., Passy, R., Waite, S. & Cook, R. (2016). Exploring School’s Use of Natural Spaces. Risk,Protection, Provision and Policy 12, 1-24. Ginsburg, H.P & Opper, S. (2016). Piaget’s Theory of Intellectual Development. Kennedy: International Psychoterapy Institute E-Books. Gough, N. (2016). Australian Outdoor (and) Environmental Education Research: Senses of ‘Place’ in Two Constituencies. Journal of Outdoor and Environmental Education 19(2), 1-11. Gunarsa, S.D. & Nigsih, Y. (2014). Psikologi Perkembangan Anak dan Remaja. Jakarta: PT TBK Gunung Mulia. Harsolumakso, A.H et al. (2019). Geology of The Eastern Part of The Volcanic-Kendeng Zone of East Java: Stratigraphy, Structures, and Sedimentation Review from Besuki and Situbondo Areas. Journal of Geology and Mineral Resources 20(3), 143-152. Hebe, H.N. (2017). Towards a Theory-driveb Integration of Environmental Education: The Application of Piaget and Vygotsky in Grade R. International Journal of Environmental & Science Education 12(6), 1525-1545. Levy, D., Peralta, T.M., Pozzi, L., & Tovar, P. (2018). Teachers Multidimensional Role Towards Meaningful Learning: The Potential Value of Interdisciplinary Environments. International Journal for Innovation Education and Research 6(2), 179-187. Miles, B & Mattchow, B. (2015). The Mirror of The Sea: Narrative Identity, Sea Kayak Adventuring and Implications for Outdoor Adventure Education. Australian of Outdoor Education 18(1), 16-26. Moleong, L. (2014). Metodologi Penelitian Kualitatif Edisi Revisi. Bandung: PT. Remaja Rosdakarya. Muhsin, A., Febriany, L.M., Hidayati, H.N., & Purwanti, Y.D. (2015). Material Bambu sebagai Konstruksi pada Great Hall Eco Campus Outward Bound Indonesia. Jurnal Reka Karsa 3 (3), 1-11. Prasetya, S.P. (2014). Media Pembelajaran Geografi. Yogyakarta: Penerbit Ombak. Rowe, N., Dadswell, R., Mudie, C., & Rauworth, M. (2014). Tall Ships Today: Their Remarkable Story. London: Adlard Coles Nautical. Sejati et al. (2017). The effect of Outdoor Study on the Geography Scientific Research Writing Ability to Construct Student Character in Senior High School. Social Sience, Education, and Humanities Research 100, 104-108. Spillman, D. (2017). Coming Home to Place: Aboriginal Lore and Place-Responsive Pedagogy for Transformative Learning in Australian Outdoor Education. Journal of Outdoor and Environmental Education 20(1), 14-24. Sudjana, N. & Rivai, A. (2015). Media Pengajaran Cetakan Ke-12 . Bandung: Sinar Baru Algensindo. Sumarmi. (2015). Model-model Pembelajaran Geografi. Malang: Aditya Media Publishing. Thomas, G.J. (2019). Effective Teaching and Learning Strategies in Outdoor Education: Findings from Two Residential Programmes Based in Australia. Journal of Adventure Education and Outdoor Learning 19(3), 242-255. Voogt, J. & Knezek, G. (2015). Guest Editorial: Technology Enhanced Quality Education for All-Outcomes from EDUsummIT 2015. Educational Technology & Society 19(3), 1-4. Zhou, M. & Brown, D. (2015). Educational Learning Theories: 2nd Edition.Georgina: Galileo Open Learning Materials. Copyright (c) 2019 Geosfera Indonesia Journal and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License